2000
DOI: 10.2135/cropsci2000.4041156x
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis of New Sources of Resistance to Erwinia carotovora ssp. atroseptica in Potato Done by AFLP, RFLP, and Resistance‐Gene‐Like Markers

Abstract: The two most important bacterial diseases of cultivated potato, blackleg of stems and tuber soft rot, are caused by Erwinia species. Genetic resistance currently present in cultivars is insufficient to protect the crop. New sources of polygenic resistance to Erwinia carotovora ssp. atroseptica (van Hall) Dye (Eca) have been selected in diploid hybrids originating from intercrossing Solanum tuberosum L with the wild species S. chacoense Bitter and S. yungasense Hawk. One F1 hybrid population derived from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 35 publications
3
62
0
Order By: Relevance
“…The gene Gm conferring resistance to Potato virus M has been recently identiWed in a similar region on potato chromosome IX (Marczewski et al 2006), as well as a QTL for resistance to Erwinia carotovora ssp. atroseptica (Zimnoch-Guzowska et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The gene Gm conferring resistance to Potato virus M has been recently identiWed in a similar region on potato chromosome IX (Marczewski et al 2006), as well as a QTL for resistance to Erwinia carotovora ssp. atroseptica (Zimnoch-Guzowska et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some SNP positions and alleles differed, however, between the five fully sequence-characterized StAOS2 alleles and the 14 StAOS2 SNPs scored in the tetraploid breeding populations of this study. This indicated that the StAOS2 alleles present in the tetraploid germplasm were not all the same as the StAOS2 alleles described in Pajerowska-Mukhtar et al (2008), which originated from diploid, more exotic germplasm generated in prebreeding programs (Oberhagemann et al 1999;Zimnoch-Guzowska et al 2000). In fact, the variation of resistance explained by StAOS2 alleles in the experimental, diploid QTL mapping populations was with 10-14% (Pajerowska-Mukhtar et al 2008), much smaller than the variance explained in the association experiment reported here (39-43% for rAUDPC; 31-36% for MCR).…”
Section: R3bmentioning
confidence: 99%
“…It is also known that the AFLP technique has lower initial costs and is more transferable across species than SSR methods. Techniques based on AFLPs have been applied to genome mapping (Zimnoch-Guzowska et al, 2000), DNA fingerprinting (Powell et al, 1996), genetic diversity studies (Russell et al, 1997) and parentage analysis (Gerber et al, 2000;Lima et al, 2001).…”
Section: Introductionmentioning
confidence: 99%